PERANAN PSIKOLOG DALAM PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA - Arief Budiarto (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2017)
In essence marriage aims to form a happy and eternal family, but in practice, sometimes the purpose of this marriage can not be achieved by various factors. In the married life, sometimes there are various problems, such as domestic violence. In such cases, it would have caused a victim to be physically as well as psychically injured. In such circumstances, much needed psychologist involvement, in addition to other law enforcement agencies to help resolve related legal cases in marriage.In cases of domestic violence a psychological approach is needed for both the perpetrator and the victim. Doers of domestic violence that can hurt the nearest person, from the point of view of psychiatric, influenced by psychiatric disorders. Domestic violence perpetrators, need to be given in-depth counseling rather than just punishment. From the side of the victim, should have the victims of domestic violence have a support system. The support system will help reduce the effects of domestic violence that the victim may experience.Support system is to seek moral help and psychological support from certain sources that are easily accessible and obtainable when the victim needs them. The role of psychologists in the field of law, among others, as advisers, evaluators and reformers.